CRIMINALISTICS TACTICS IN CASE OF CATASTROPHIC PLANE DISASTER - Nicolae MĂRGĂRIT (Challenges of the Knowledge Society)
This article is showing the criminalistics tactics in case of catastrophic plane disaster. It was analysed the crime scene investigation and the criminalistic methods of research of the victims in case of a plane disaster. The catastrophic plane disaster can be seen as a crash of an air plane after a collision between two planes, a collision with other obstacles, or other types of disaster if it generates the consequences of death or injured people, or plane and goods destruction and it is a crime referred to in the Air Transport Code. Catastrophic disaster is a tragic event, of great proportions, with no advance notice, with disastrous consequences. The catastrophic disaster is a generic notion. In practice there are two major catastrophic groups: natural catastrophes and disasters. Natural catastrophes are natural phenomena that occur according to physical laws and arise as a result of a brutal, but passive imbalance between the factors underlying these physical laws, predictable as manifestations, unpredictable as a moment of occurrence, observing as tragic events of great proportions and disastrous consequences on social - economic level. The disasters represent the catastrophe group in whose’s production is incriminated the direct or indirect action, voluntary or involuntary of human being. Concluding, we can say that through catastrophe we understand all-natural phenomena, unexpected damage or accidents that hit a city, a country or a group of people linked by labour relations or during a trip and whose combat requires a large supply of people and means.